Şanzımanlarda Dişli Oranı Değişiminin Analizi - Aysal, Faruk Emre; Bayrakçeken, Hüseyin; Girgin, Zekeriya (Afyon Kocatepe Üniversitesi, 2015)
Taşıt dinamiğini ilgilendiren en önemli güç aktarma organlarında biri şanzımandır. Araştırmacılar yakıt tüketimini azaltmak, sürüş konforunu arttırmak ve taşıtın performansını iyileştirmek gibi amaçlarla şanzımanların geliştirilmesi çalışmaktadır. Yapılan çalışmalarda simülasyon ortamı olarak Msc. Adams, AMSim gibi birçok farklı program kullanılmıştır. Bu programların başında ise Matlab/Simulink gelmektedir. Bu çalışmada dişli oranlarının taşıta olan etkilerini incelemek amacıyla Matlab/Simulink ortamında simülasyonlar hazırlanmıştır.

One of the most important powertrain, which is related to Vehicle Dynamics, is transmissions. Researchers are working to develop transmissions due to reduce fuel consumption, enhance driving comfort and improve vehicle performance. In the previous studies have been used many different simulation programs such as Msc. Adams and AMSim as a simulation environment. The most widely used simulation program for vehicle dynamics is Matlab/Simulink. In this paper, simulations were prepared in the Matlab/Simulink in order to investigate the effect of gear ratios on the vehicle.
The Analysis of the Gear Ratio Variation on the Transmissions
Keywords: Taşıt Dinamiği; Şanzıman; Dişli Oranı; Simülasyon